2010
DOI: 10.1124/dmd.110.035345
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in UDP-Glucuronosyltransferase 2B17 Expression and Activity

Abstract: ABSTRACT:UDP-glucuronosyltransferases (UGTs) are enzymes involved in the metabolism of steroid hormones, carcinogens, cancer chemotherapy agents, and addictive agents from cigarettes. Because the UGT2B family of genes has been linked to hormonal regulation in human cell lines in vitro, we hypothesized that there may be sexrelated differences in the expression and activity of these genes in human tissues. To evaluate whether there are sex differences in UGT2B expression and activity, we examined 103 normal huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 27 publications
6
45
0
Order By: Relevance
“…Individuals homozygous for UGT2B17-insertion allele (ins/ins) have been shown in previous study not to differ in liver mRNA expression as compared with ins/del in adult human liver samples (Gallagher et al, 2010). In agreement with this, we did not observe any difference in UGT2B17 mRNA levels between ins/del and ins/ins in the fetal or in the adult liver samples.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Individuals homozygous for UGT2B17-insertion allele (ins/ins) have been shown in previous study not to differ in liver mRNA expression as compared with ins/del in adult human liver samples (Gallagher et al, 2010). In agreement with this, we did not observe any difference in UGT2B17 mRNA levels between ins/del and ins/ins in the fetal or in the adult liver samples.…”
supporting
confidence: 79%
“…Therefore one may speculate that the UGT2B17 deletion polymorphism has a higher impact on the UGT2B17 gene expression in extrahepatic tissues. In addition to genetic variation, gender has been shown to affect the mRNA expression levels of UGT2B7, 2B15, and 2B17 (Ramirez et al, 2008;Gallagher et al, 2010;Ekström et al, 2012). We did not observe any differences in UGT2B gene expression between the sexes among the adult liver samples.…”
mentioning
confidence: 43%
“…Although polymorphisms in the UGT genes and altered transcriptional regulation can contribute to altered expression and/or activity of UGT1A enzymes (Wiener et al, 2004;Hoskins et al, 2007;Chen et al, 2010;Gallagher et al, 2010), these mechanisms do not explain the observations that UGT1A mRNA and protein levels often do not correlate (Izukawa et al, 2009;Oda et al, 2012;Ohtsuki et al, 2012) and that there is a high degree of variability in UGT mRNA and protein expression within different tissues and between different individuals (Izukawa et al, 2009;Ohno and Nakajin, 2009). Such observations suggest an epigenetic mechanism of posttranscriptional regulation may be affecting UGT protein expression.…”
Section: Introductionmentioning
confidence: 69%
“…Gallagher et al 3 showed that there are sex differences in UGT2B expression and activity, with men exhibiting a higher level of expression of UGT2B17 and a higher level of glucuronidation activity than women. Moreover, the condition of UGT2B17 mismatch by itself assumes the presence of at least one UGT2B17 allele in the recipient.…”
Section: Discussionmentioning
confidence: 99%
“…2 Interestingly, it has been described that men have higher UGT2B17 expression and activity than women. 3 The human UGT2B17 gene varies in copy number from zero to two per individual because of the presence of a polymorphism that consists of a 129-kb deletion. 4 The incidence of this gene deletion varies among populations on the basis of their ethnic background.…”
mentioning
confidence: 99%